PERBANDINGAN METODE CBR, NN-5 DAN NAÏVE BAYES UNTUK KLASIFIKASI INFEKSI NOSOKOMIAL - Taufiq Rizaldi; Aji Seto Arifianto (Jurnal Teknologi Informasi dan Terapan, 2019)
Classification method is a method that is widely used for the completion of the diagnosis of disease, particularly in humans. One type of disease that is dangerous is potentially emerging nosocomial infection in patients postoperatively. Approach classification method based upon the similarity of character data, there is also a reference to the emergence of statistical data. Some methods of classification needs to be tested in order to obtain the appropriate reference method for this case. The purpose of this study was to compare the performance of three methods of classification that Case Based Reasoning method (CBR), Neirest Neighbor-5 (NN-5) and Naïve Bayes for diagnosis of nosocomial infection. Test results showed that the method of CBR and NN-5 has a very good degree of accuracy than Naïve Bayes, Naïve Bayes but has a faster processing time.